Modified Technique for Repairing Recurrent Pulmonary Venous Obstruction - Kazunari Fujisawa, BSc; Hideyuki Kato, MD; Bryan J. Mathis, PhD; Yuji Hiramatsu, MD (Annals of Thoracic Surgery Short Reports)
Postoperative pulmonary venous obstruction after the repair of total anomalous pulmonary venous connection is a challenging complication, especially when it occurs in the upstream pulmonary vein outside the pericardial sac. Here, we report such a case that was resolved successfully by a novel, modified, sutureless technique that repositioned the pericardial reflection to expand the pericardial sac.